PENGELOLAAN ARSIP LEMBAGA PEMERINTAHAN: STUDI PADA DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN CILACAP - ALBERTOES PRAMUKTI NARENDRA (Jurnal Ilmiah Widya Sosiopolitika, 2021)
Every organization, both government and private, in the process of its activities willproduce a record of activity information which is called an archive. In organizationallife, there are dynamic archives and static archives. The management of this type ofarchive is different considering that each has a different use value. This study wants toknow more deeply about archive management in government institutions, especially atthe Dinas Kearsipan dan Perpustakaan Kabupaten Cilacap which also receivedrecognition for its achievements. This study uses a descriptive qualitative method withinterviews with archivists. The results of this study note that archive management ingovernment institutions is regulated by various government guidelines and regulations.Archival services are also developed based on information technology. The managementof static archives, especially in the form of archive acquisition, is carried out in agenciesthat are disbanded, merged and/or liquidated. The acquisition is carried out on archivesthat have static value and or have retention of more than 10 years.